2012
DOI: 10.1021/jp212558p
|View full text |Cite
|
Sign up to set email alerts
|

Stable, Single-Layer MX2 Transition-Metal Oxides and Dichalcogenides in a Honeycomb-Like Structure

Abstract: Recent studies have revealed that single-layer transition-metal oxides and dichalcogenides (MX 2 ) might offer properties superior to those of graphene. So far, only very few MX 2 compounds have been synthesized as suspended single layers, and some of them have been exfoliated as thin sheets. Using first-principles structure optimization and phonon calculations based on density functional theory, we predict that, out of 88 different combinations of MX 2 compounds, several of them can be stable in free-standing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

93
1,055
7
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,276 publications
(1,175 citation statements)
references
References 123 publications
93
1,055
7
8
Order By: Relevance
“…2. Accordingly, our method is not only able to clearly demonstrate the electronic band structure of defective MoS 2 and WS 2 monolayers, but also is very computationally affordable and can be easily generalized to study very large systems with a random distribution of single defects and other types of vacancies such as MoS double vacancies, MoS 2 triple vacancies and antisite defects 2,18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Accordingly, our method is not only able to clearly demonstrate the electronic band structure of defective MoS 2 and WS 2 monolayers, but also is very computationally affordable and can be easily generalized to study very large systems with a random distribution of single defects and other types of vacancies such as MoS double vacancies, MoS 2 triple vacancies and antisite defects 2,18 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the model presents an accurate description for the band structure of LTMDs, the application of this model to defective MoS 2 and WS 2 provides a more realistic understanding of the electronic states contributing to the process of vacancy formation and the accurate location of defect states within the bandgap. Moreover, the optimized geometries of the monolayers obtained by ab initio calculations have demonstrated that atomic vacancies do not cause a considerable geometry deformation and the neighboring atoms around the vacancies do not show any visible displacement 2,22 . Therefore, the defect-induced deformation is ignored.…”
Section: Introductionmentioning
confidence: 98%
“…Many TMDCs have band structures that are similar in their general features, as shown by first principles and tight-binding approximations 25,[80][81][82][83][84][85] and measured using a variety of spectroscopic tools 31,32,[86][87][88][89] . In general, MoX 2 and WX 2 compounds are semiconducting whereas NbX 2 and TaX 2 are metallic 25,[80][81][82][83][84] .…”
Section: Electronic Structurementioning
confidence: 99%
“…In general, MoX 2 and WX 2 compounds are semiconducting whereas NbX 2 and TaX 2 are metallic 25,[80][81][82][83][84] . The band structures of bulk and monolayer MoS 2 and WS 2 calculated from first principles are shown in Fig.…”
Section: Electronic Structurementioning
confidence: 99%
“…This stimulated the search for other families of semiconducting layered materials. Among them, transition metal dichalcogenides (TMD) [7] are probably the materials with the most versatile electronic properties [8,9]. Their chemical formula is MX 2 , where M is a transition metal and X a chalcogen (S, Se, and Te).…”
Section: Introductionmentioning
confidence: 99%